Ergonomics study and analysis of flexible manufacturing system - Norqadrulnida Zakaria (Universiti Malaysia Perlis, 2008)
Nowadays, the market trend has been demanding increased diversity in product offerings, along with frequent updates to each product. This in turn is influencing manufacturing to invest in more flexible equipment for new programs. The report will emphasis on the interaction between the human and machine for which in this case it focus on Flexible Manufacturing System in UniMAP laboratory. It will cover the ergonomics feature in the UniMAP flexible manufacturing system lab and also the working behavior of the human working in this work environment. The element of the flexible manufacturing system such as the robotic arm, CNC machine, conveyer, pallet, and storage rack will be define to identify the areas of human involvement in the system. It is crucial to study on the human posture because the working behavior will tend to affect the performance of the workers. The idea behind ergonomics is to reduce physical strain by designing or modifying the work station, work methods, and tools in an attempt to eliminate excessive stress and strain, reduce awkward postures and to decrease the number of repetitive motions needed to get the job done. Particular emphasis is also placed on the design of the human-machine interface to ensure increase safety and usability of equipment and the removal of harmful stresses.